Literature Based-Communication in Enhancing EFL Students' Intercultural Awareness through Implementing ICC Model - Nazenin Shekh Muhemad Bapir; Nada Jabbar Abbas; Shireen Sadallah Rashid (Zanco Journal of Humanity Sciences)
This study investigates the role of teaching literature based-communication in enhancing EFL students’ intercultural awareness through applying Byram’s model of ICC (1997) and the revised version (2020). The study is an empirical with two random groups, control (CG) and experimental group (EG). It aims at examining literature based-communication in enhancing EFL students' intercultural awareness and also aims at detecting the difference between the control and experimental groups' (five element factors). For data collection, a pre-post-test is used. EG received the ICC model and various teaching strategies, while CG is taught traditionally. 2 groups are exposed to the same teaching materials. The participants are 60 second-year English students (30 CG and 30 EG) of English department. The mean score, SD, t-test, and p-value are conducted. The progress is in EG’s post-test compared to the results of CG. The huge progress in five element factors is in the EG’s post-test compared to the results of CG as there is a significant difference of EG post-test in favor of ICC in enhancing  intercultural awareness to which the EG was exposed to during the experiment.